Determinants of Profitability in Indonesian Logistics Companies: An Analysis of Operational Cost Efficiency, Pricing Strategies, and Government Policies - Mochammad Subagio (Siber Nusantara of Economic and Finance Review, 2026)
This study aims to analyze the determinants of profitability for companies in the logistics sector in Indonesia through a comprehensive review of operational cost efficiency, pricing strategies, and government policies. The method used was a  Literature Review, integrating findings from 30 reputable scientific articles sourced from international and national journals between 2021 and 2026. The results indicate that operational cost efficiency, adaptive pricing strategies, and government policy support have a significant impact on improving the profitability of logistics companies. This study provides a theoretical contribution to mapping the financial performance of the logistics sector as well as managerial recommendations for policymakers.